Inoculum size and traits of the infecting clinical strain define the protection level against Mycobacterium tuberculosis infection in a rabbit model. Issue 6 (20th March 2020) - Tsenova, Liana; Fallows, Dorothy; Kolloli, Afsal; Singh, Pooja; O'Brien, Paul; Kushner, Nicole; Kaplan, Gilla; Subbian, Selvakumar
Abstract: Host protective immunity against pathogenic Mycobacterium tuberculosis (Mtb) infection is variable and poorly understood. Both prior Mtb infection and BCG vaccination have been reported to confer some protection against subsequent infection and/or disease. However, the immune correlates of host protection with or without BCG vaccination remain poorly understood. Similarly, the host response to concomitant infection with mixed Mtb strains is unclear. In this study, we used the rabbit model to examine the host response to various infectious doses of virulent Mtb HN878 with and without prior BCG vaccination, as well as simultaneous infection with a mixture of two Mtb clinical isolates HN878 and CDC1551. We demonstrate that both the ability of host immunity to control pulmonary Mtb infection and the protective efficacy of BCG vaccination against the progression of Mtb infection to disease is dependent on the infectious inoculum. The host response to infection with mixed Mtb strains mirrors the differential responses seen during infection with each of the strains alone. The protective response mounted against a hyperimmunogenic Mtb strain has a limited impact on the control of disease caused by a hypervirulent strain. This preclinical study will aid in predicting the success of any vaccination strategy and in optimizing TB vaccines. Abstract : Using a rabbit model of pulmonary tuberculosis, we demonstrate that the degree of protective immunity against  Mycobacterium tuberculosis infection is defined by the inoculum size and the nature of infecting strain. Protection conferred by prior BCG vaccination is limited and additive to immunity induced by exposure to the infectious inoculum.